The Preface of Serving the People: Selected Works of Gennady Zyuganov: History in the Archives of Time (World Marxist Review, 2025)
The preface of “Serving the People: Selected Works of Gennady Zyuganov” summarizes the development and challenges of the Communist Party of the Russian Federation over the past 30 years, emphasizing the core role of Marxism-Leninism and Gennady Zyuganov’s contributions to thought. The article highlights the achievements of the CPRF in protecting the interests of the working class, resisting external reactionary forces, and uniting international leftist movements, as well as its close ties with friendly countries, showcasing the party’s ongoing struggle and mission in the new era.